2018
DOI: 10.1038/s41467-018-04686-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species regulate the induction of CD8+ T cells by plasmacytoid dendritic cells

Abstract: Cross-presentation allows exogenous antigen presentation in association with major histocompatibility complex class I molecules, a process crucial for the priming of CD8+ T-cell responses against viruses and tumors. By contrast to conventional dendritic cells (cDC), which cross-present antigens in the steady state, plasmacytoid dendritic cells (pDC) acquire this ability only after stimulation by Toll-like receptor (TLR) ligands. The intracellular pathways accounting for this functional difference are still unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 48 publications
2
83
0
Order By: Relevance
“…α-Glucans in Mycobacterium tuberculosis can induce ROS production and lead to DC maturation and lymphocyte proliferation, which is partly related to the induction of spleen tyrosine kinase (Syk) ( 132 ). The reduction in mitochondrial ROS production dramatically decreases the cross-presentation capacity of pDC and strongly impairs their ability to trigger CD8 + T cell responses ( 133 ). Mogilenko et al also report that reducing mitochondrial ROS production in DC ameliorates the disease in an IL-23-dependent model of psoriasis because of the reduction in IL-23 and skin inflammation ( 130 ).…”
Section: The Metabolism Modification Of Tol-dcmentioning
confidence: 99%
“…α-Glucans in Mycobacterium tuberculosis can induce ROS production and lead to DC maturation and lymphocyte proliferation, which is partly related to the induction of spleen tyrosine kinase (Syk) ( 132 ). The reduction in mitochondrial ROS production dramatically decreases the cross-presentation capacity of pDC and strongly impairs their ability to trigger CD8 + T cell responses ( 133 ). Mogilenko et al also report that reducing mitochondrial ROS production in DC ameliorates the disease in an IL-23-dependent model of psoriasis because of the reduction in IL-23 and skin inflammation ( 130 ).…”
Section: The Metabolism Modification Of Tol-dcmentioning
confidence: 99%
“…cDC1 development is dependent on several key transcriptional factors, such as BATF3, IRF8, ZBTB46, ID2, and ETV6 ( Aliberti et al, 2003 ; Hacker et al, 2003 ; Hildner et al, 2008 ; Meredith et al, 2012a , b ; Sichien et al, 2016 ; Lau et al, 2018 ). In addition to cDC1s, DCs derived under inflammatory conditions from hematopoietic progenitors or monocytes, and activated plasmacytoid DCs (pDCs), are also capable of cross-presentation ( Helft et al, 2015 ; Oberkampf et al, 2018 ). In general, cross-presentation of exogenous antigens can occur via two major pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic cells have specialized antigen presentation functions that are involved in activating T cell immunity, specifically CD4 + and CD8 + responses (4,36). Several recent studies have demonstrated mtROS, in particular H 2 O 2 regulates the induction of CD8 + T cells and the antigen presentation by plasmacytoid DCs to CD8 + T cells (29). These observations do not appear consistent with our findings, as we observed no alterations in the IAV-induced activation of both lung and splenic CD8 + and CD4 + T cell responses with MitoTEMPO treatment at the early and later stages of infection.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that there is a high degree of redundancy in the mtROS-dependent activation of Ag cross-presentation (29). This is evident in studies that have utilized mtROS scavengers at different concentrations resulting in graded reductions in mtROS (29). For example, partial suppression of mtROS with S3QEL2, a mitochondrialtargeted antioxidant, had no effect on the cross-presentation capacity of pDC (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation